The efficiency of inspection based on out of control detection in wafer fabrication. (September 2016) - Tirkel, Israel
Highlights: This work presents a novel approach for modeling the efficiency of inspection in wafer fabrication. Out of control performance versus inspection rate exhibits a convex curve, minimizing out of control. Inspection efficiency curve illustrates the relationship between out of control performance and inspection capacity. Quality output, driven by reduced out of control, grows with increasing inspection capacity at a slower pace. Cost efficient inspection is determined by: inspection capacity, inspection rate, out of control. Abstract: This work proposes an approach for modeling the efficiency of in-line inspection in semiconductor wafer fabrication. Clearly, improved quality generates increased quality output, and thus higher income from sales. Yet, it also requires increased fault detection enabled by more inspection capacity, and thus higher cost. This work investigates the efficiency of inspection by evaluating the gain from quality output against the corresponding cost incurred. It is based on a production model of wafer fabrication, where wafer lots are sampled for inspection following their process by machines. The inspection detects out of control performance and triggers machine repair. Thus, quality performance improves as a function of the rate of inspection and the duration of response. Based on Pareto efficiency, the inspection efficiency curve is developed illustrating the relationship between quality performance and inspection capacity. It exhibits that quality output, driven by reduced out of control performance, grows with inspection capacity at a slower pace. Furthermore, incremental quality output and incremental inspection cost determine the most efficient working point. This point designates inspection capacity, inspection rate, and resultant quality performance. The novelty of this work is in suggesting a quantitative model for designing the efficiency of inspection in wafer fabrication.